2019
DOI: 10.2217/epi-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of microRNAs in coronary Atherosclerotic Plaque

Abstract: Aim: Identification of microRNAs (miRNAs) associated with atherosclerosis may unravel novel therapeutic targets and biomarkers. We studied miRNAs differentially expressed between coronary atherosclerotic plaques (CAP) and healthy arteries. Materials & methods: Paired CAP and internal mammary arteries (IMA) were collected from 14 coronary artery disease patients. The miRNA profiles between diseased (CAP) and healthy (IMA) tissues were compared using microarrays and quantitative PCR. Results: Thirty-one miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Previous studies have been conducted to identify therapeutic targets for UA, most of which have been limited to protein-coding genes, miRNAs and lncRNAs (32)(33)(34)(35). Recently, circRNAs have attracted attention as new diagnostic markers for diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been conducted to identify therapeutic targets for UA, most of which have been limited to protein-coding genes, miRNAs and lncRNAs (32)(33)(34)(35). Recently, circRNAs have attracted attention as new diagnostic markers for diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 high abundance was observed in macrophages [ 70 ] and was revealed to affect foam cell formation [ 71 ]. Berkan et al found that the formation of atherosclerotic plaque was associated with miR-486-5p downregulation [ 72 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Regulation of microRNAs in coronary atherosclerotic plaque [72] miR-486-5p Formation of atherosclerotic plaque is associated with miR-486-5p downregulation. Circulating miR-146a may be a potential biomarker of coronary heart disease in patients with subclinical hypothyroidism [73] miR-146a miR-146a is a possible predictor of atherosclerosis and its severity in patients with hypothyroidism and raised TSH level.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific publications published on behalf of the EU-CardioRNA COST Action included two or more member authors from at least two different COST member states or partner countries. Three scientific papers, in addition to the previously mentioned EU-CardioRNA project report, had been published (until 16 October 2019) [30][31][32].…”
Section: Wg4 Sessionmentioning
confidence: 99%